Search for anomalous couplings in the Higgs sector at LEP - Achard, P. (2004)
Anomalous couplings of the Higgs boson are searched for through the processes e+e− → Hγ , e+e− → e+e−H and e+e− → HZ. The mass range 70 GeV < mH < 190 GeV is explored using 602 pb−1 of integrated luminosity collected with the L3 detector at LEP at centre-of-mass energies √s = 189–209 GeV. The Higgs decay channels H → f¯f, H → γ γ , H → Zγ and H → WW(∗) are considered and no evidence is found for anomalous Higgs production or decay. Limits on the anomalous couplings d, dB, gZ 1 , κγ and ξ 2 are derived as well as limits on the H → γ γ and H → Zγ decay rates